Tuberculosis of the breast and the differential diagnosis with cancer problem. Study of 30 cases - Misad N, Oscar (2015)
We report 30 cases of tuberculosis of the breast observed among 1,023 male and female patients who consulted at the National Institute of Neoplastic Diseases with the presumption of being carriers of mammary tumors. Tuberculosis of the breast in our study represents 2.94 percent of all breast lesions. The disease has been observed in all ages, most frequently between 30 and 40 years; 67 percent of cases was included in this decade. The clinical course of the disease goes through the stages of nodule, skin adhesion and fistula, with or without lymphadenopathy. From the viewpoint of differential diagnosis with carcinoma of the breast, it is possible to distinguish two periods: an initial one which shares many of the physical signs of carcinoma, and other subsequent, very characteristic that identifies with the stage of fistula and which can make the correct diagnosis. The pathological study of the lesion is necessary to establish the nature of the disease condition. Although relatively few cases studied, it can be said that the treatment of choice for breast tuberculosis is surgical and that better results are obtained when associated with specific medical treatment. When medical treatment was administered, but good results were obtained in 66.5 percent of cases; the percentage rose to 85 percent when surgical treatment was used alone, and 100 percent when both treatments were combined. Methods of diagnosis of breast lesions in use at the National Institute of Neoplastic Diseases, has again exposed the usefulness of aspiration biopsy: of the 9 patients with clinical diagnosis of carcinoma in 7 addition rule existence of a neoplastic process, suggested the possibility of tuberculosis infection.